Mapping Experimental and Theoretical Reactivity Descriptors of Fe Macrocyclic Complexes Deposited on Graphite or on Multi Walled Carbon Nanotubes for the Oxidation of Thiols: Thioglycolic Acid Oxidation - Zagal-Moya, J; Zagal-Moya, J; Oyarzun-Medina, M; Oyarzun-Medina, M; Ramírez-Pastén, S; Ramírez-Pastén, S (Elsevier Ltd, 2021)
We have studied the electro-oxidation of thioglycolic acid (TGA) catalyzed by iron phthalocyanines and iron porphyrins (FeN4 complexes) deposited on ordinary pyrolytic graphite and on multiwalled carbon nanotubes. The purpose of this work is to establish both experimental and theoretical reactivity descriptors of MN4 macrocyclic complexes for electrooxidation of thioglycolic acid (TGA) as an extension of previous studies involving other reactions using these types of catalysts. Essentially, the reactivity descriptors are all related to the ability of the metal center in the MN4 moiety to coordinate an extra planar ligand that corresponds to the reacting molecule. This coordinating ability, represented by the M-TGA binding energy can be modulated by tuning the electron-donation ability of the ligand and it is linearly correlated with the Fe(III)/(II) redox potential of the complex. Experimental plots of activity as (log j)E at constant potential versus the Fe(III)/(II) redox potential of the MN4 catalysts give volcano correlations. A semi-theoretical plot of catalytic activities (log j)E vs DFT calculated Fe-TGA binding energies (EbTGA) is consistent with the experimental volcano-type correlations describing both strong and weak binding linear correlations of those volcanos. On the other hand, the Hirshfeld population analysis shows a positive charge on the Fe center of the FeN4 complexes, indicating that electron transfer occurs from the TGA to the Fe center in the FeN4 complexes that act as electron acceptors. The donor (TGA)-acceptor (Fe) intermolecular hardness ΔηDA was also used as reactivity descriptor and the reactivity of the Fe centers as (log j)E increase linearly as ΔηDA increases. If activity is considered per active site, the trends is exactly the opposite, i.e. a plot of (logTOF)E increases linearly as ΔηDA decreases as expected form the Maximum Hardness-Principle. A plot of (logTOF)E versus E°’Fe(III)/(II) gives a linear correlation indicating that the activity per active site increases as the redox potential decreases. © 2021